Metaverse as Medium: Understanding the Revival of McLuhan’s Notion ’Medium is the Message’ in the Emergent Virtual Reality Landscape - Rashid, Muhammad; Khan, Musa (Journal of Communication and Cultural Trends, 2024)
This research aims to explore the advent of Metaverse as a medium in the emergent virtual reality landscape. It draws on the work of media theorist Marshall McLuhan related to the relationship among human beings, society, culture, and technology defined under the term “the medium is the message". The study examines the possible revival of McLuhan’s notion in the Age of Metaverse, as well as in other virtual worlds. Metaverse is an emerging technology of shared virtual spaces that combine virtual reality, augmented reality, mixed reality, and other immersive technologies. Following the notions of medium theory and technological determinism as analytical frameworks, the study provides detailed insights about the influence of new technologies reshaping people’s perception as well as theunderstanding of new communication tools and media. The research is based on the systematic literature review method. The findings present the current state of research on Metaverse and virtual reality including their usage and applications within the framework of McLuhan’s media theories. The review identifies several themes that emerge from the literature, including the Extension of Man, the Global Village, McLuhan’s new medium, and the medium is the message in the virtual age. The results suggest that Metaverse, as a new form of immersive medium, continues to emerge and shape human communication and social interactions.